Effect of agonists of adenosine receptors on inflammatory markers in human Muller cells - Kumar, S.; Safi, S.Z.; Qvist, R.; Ismail, I.S. (2014)
We report the presence of adenosine receptors at molecular level and study their role in the inflammatory pathway under hyperglycemic condition. Human Muller cells were cultured in low (5 mM) and high (25 mM) glucose with 10 FBS and 1 P/S. Cells were starved in 0 FBS for 18 h and then treated with various agonists CCPA, CGS 21680, NECA and IB-MECA for 6, 12 and 24 h. The adenosine receptors were identified by immunocytochemistry. ELISA was used to measure the levels of TNF-alpha, IL-1 beta and ICAM 1. Four types of adenosine receptors (A(1), A(2A), A(2B) and A(3)) were identified in human Muller cells. TNF-alpha content increased after agonist A(1) and A(3) treatment, but decreased after agonist A(2A) and An treatment. There was no significant effect on ICAM-1 and IL-1 beta. Stimulation of human Muller cells with adenosine A(2A) agonist (CGS 21680) and adenosine A(2B) agonist (NECA) reduces the level of TNF-alpha when exposed to high glucose, whereas A(1) adenosine agonist (CCPA) and A(3) adenosine agonist (IB-MECA) both positively and negatively regulate the TNF-alpha in hyperglycemia. However, none of these agonists has any significant role in affecting ICAM-1 and IL-1 beta.